2023
DOI: 10.3390/biotech12020032
|View full text |Cite
|
Sign up to set email alerts
|

Post-Harvest Prevention of Fusariotoxin Contamination of Agricultural Products by Irreversible Microbial Biotransformation: Current Status and Prospects

Abstract: Biological degradation of mycotoxins is a promising environmentally-friendly alternative to chemical and physical detoxification methods. To date, a lot of microorganisms able to degrade them have been described; however, the number of studies determining degradation mechanisms and irreversibility of transformation, identifying resulting metabolites, and evaluating in vivo efficiency and safety of such biodegradation is significantly lower. At the same time, these data are crucial for the evaluation of the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 155 publications
(267 reference statements)
0
3
0
Order By: Relevance
“…According to a recent report, DON has been found in up to 81% of cereals and cereal products in Africa; even in South America, where concentrations are lowest, the percentage was as high as 46%. 2 The maximum contamination of DON is as high as 6500 μg/kg in contaminated grain, well above the maximum limits set by the World Health Organization (WHO). 3 DON is also carcinogenic, teratogenic, and mutagenic and was classified as a Group III carcinogen by the WHO in 2017.…”
Section: ■ Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…According to a recent report, DON has been found in up to 81% of cereals and cereal products in Africa; even in South America, where concentrations are lowest, the percentage was as high as 46%. 2 The maximum contamination of DON is as high as 6500 μg/kg in contaminated grain, well above the maximum limits set by the World Health Organization (WHO). 3 DON is also carcinogenic, teratogenic, and mutagenic and was classified as a Group III carcinogen by the WHO in 2017.…”
Section: ■ Introductionmentioning
confidence: 94%
“…The high rate of contamination and toxicity of DON make it a serious threat to global food security. According to a recent report, DON has been found in up to 81% of cereals and cereal products in Africa; even in South America, where concentrations are lowest, the percentage was as high as 46% . The maximum contamination of DON is as high as 6500 μg/kg in contaminated grain, well above the maximum limits set by the World Health Organization (WHO) .…”
Section: Introductionmentioning
confidence: 99%
“…First, any mycotoxins that were produced may have been biodegraded immediately subsequent to their production. Numerous studies have shown that pure or heterogenous microbial cultures isolated from different environments are capable of irreversibly transforming DON and other mycotoxins into less toxic compounds [15]. Composting alone or in combination with anaerobic digestion has also been shown to be an effective method of removing mycotoxins from contaminated substrates [16,17,72].…”
Section: Trace Amounts Of Mycotoxins Found During Composting Of Biowa...mentioning
confidence: 99%
“…The limited number and scope of such studies might be due to the assumption that mycotoxins are naturally degraded to less harmful products. However, most studies on mycotoxin degradation only tested the ability of isolated strains of bacteria or fungi under in vitro conditions, not in realistic scenarios [15]. To the best of our knowledge, the ability of the composting process to degrade mycotoxins has only been tested for aflatoxin B1 [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Present in plant material, DON and ZEN belong to a large group of fusarium mycotoxins [ 8 ] which are produced by various fungal species, including Fusarium , Myrothecium , Cephalosporium , Verticimonosporium and Stachybotrys [ 3 ]. To date, the following mechanisms of toxicity of these mycotoxins have been identified in cells or proteins: (i) DON binds to the 60S ribosome subunit at the molecular level and induces ribotoxic stress, which activates protein kinase and, consequently, inhibits protein synthesis, and provokes endoplasmic reticulum stress [ 9 ], cell signalling, cell differentiation, cell proliferation and cell death [ 5 , 10 ]; (ii) ZEN [ 11 ] exerts toxic effects by binding to and activating both ERs, disrupting the cell cycle and inducing DNA fragmentation, which leads to the production of micronuclei and chromosomal aberrations [ 4 , 5 , 10 ].…”
mentioning
confidence: 99%